Cytokines TNF-α, IL-6, IL-17F, and IL-4 Differentially Affect Osteogenic Differentiation of Human Adipose Stem Cells - Angela P. Bastidas-Coral; Astrid D. Bakker; Behrouz Zandieh-Doulabi; Cornelis J. Kleverlaan; Nathalie Bravenboer; Tim Forouzanfar; Jenneke Klein-Nulend (Stem Cells International)
During the initial stages of bone repair, proinflammatory cytokines are released within the injury site, quickly followed by a shift to anti-inflammatory cytokines. The effect of pro- and anti-inflammatory cytokines on osteogenic differentiation of mesenchymal stem cells is controversial. Here, we investigated the effect of the proinflammatory cytokines TNF-α, IL-6, IL-8, and IL-17F and the anti-inflammatory cytokine IL-4 on proliferation and osteogenic differentiation of human adipose stem cells (hASCs). hASCs were treated with TNF-α, IL-6, IL-8, IL-17F, or IL-4 (10 ng/mL) for 72 h mimicking bone repair. TNF-α reduced collagen type I gene expression but increased hASC proliferation and ALP activity. IL-6 also strongly enhanced ALP activity (18-fold), as well as bone nodule formation by hASCs. IL-8 did not affect proliferation or osteogenic gene expression but reduced bone nodule formation. IL-17F decreased hASC proliferation but enhanced ALP activity. IL-4 enhanced osteocalcin gene expression and ALP activity but reduced RUNX2 gene expression and bone nodule formation. In conclusion, all cytokines studied have both enhancing and reducing effects on osteogenic differentiation of hASCs, even when applied for 72 h only. Some cytokines, specifically IL-6, may be suitable to induce osteogenic differentiation of mesenchymal stem cells as a strategy for enhancing bone repair.